Respiratory syncytial virus vaccination during pregnancy and effects in infants - Madhi, SA; Polack, FP; Piedra, PA; Vatish, M; Snape, M; Prepare Study Group (Massachusetts Medical Society, 2020)
BACKGROUND Respiratory syncytial virus (RSV) is the dominant cause of severe lower respiratory tract infection in infants, with the most severe cases concentrated among younger infants.